Blockchain Merkle Tree - Bo'riboyevna, Absalamova Go'zal (International Journal of Human Computing Studies, 2023)
In this research, the Blockchain Merkle Tree, which plays a decisive role in ensuring the integrity and security of data in the blockchain network, is analyzed. The Merkle Tree, also known as a hash tree, is a fundamental concept in blockchain technology. Named after Ralph Merkle, the Merkle Tree is a hierarchical data structure composed of cryptographic hash functions. The Merkle Tree provides several benefits in a blockchain context. First and foremost, it allows for efficient verification of data integrity. Instead of needing to validate each and every transaction in a block, a participant can simply verify the Merkle root and a small number of other hashes in the tree to ensure that the data hasn't been tampered with.